Process methodology for semiconductor parametric extraction and analysis - Lim, Shihui. (2013)
The purpose of this report is to provide a summary of the Final Year Project (FYP) that is done together with a researcher. In this report, the characterization of the laser etch facet during fabrication, characterization of the laser performance and creation of the light intensity measurement LabVIEW program would be explained. Learning of new programming language such as LabVIEW, setting up of laser measurement and experiencing cleanroom fabrication environment processes such as baking, dry and wet etching and etc. was part and parcel of my FYP. The projects include optimizing the etch sidewall with the characterization, researching for new etching recipe, creating new measuring program application for the ease of all users and interpreting of results from the measurement characterization. Researching new etch recipes such as what are the gases should be used and other parameters to consider. For the measurement, based on the research done, different parameters can be extracted out from the results and using these parameters to determine whether if the laser device is function at its expected performance. When problems such as programming or research issue arise, with the researcher’s guidance, the problems can quickly be resolved.